Studi Kelayakan Klinik Pajak Bagi UMKM di Kota Batam - Nurul Puan Sari; Arniati Arniati; Ria Anggraini; Dedi Kurniawan; Wika Arsansti Putri; Anjelina Anjelina; Afriyanti Hasanah (JURNAL AKUNTANSI, EKONOMI dan MANAJEMEN BISNIS, 2022)
Activities to support the government's tax digitization program can be done in some ways, one of which is by opening a tax clinic service aimed at tax-compliant MSMEs, so that it can help accelerate this program to the public. As a new tax service center that will be developed, the tax clinic must prepare everything needed so that it can be said to be appropriate and accepted by consumers. This feasibility study aims to assess the feasibility of building a tax clinic. This study method was carried out qualitatively, where the research data was obtained by observing, interviewing, and studying the literature. After the interview process, a feasibility analysis was carried out in the form of a SWOT analysis, management aspects, market and marketing aspects, legal aspects, and technical and technological aspects as well as financial aspects after which conclusions were concluded. The results of this study show that based on several aspects investigated, this tax clinic is feasible to run, but the tax clinic needs to implement a SWOT strategy that is more optimal for sustainability and responding to threats that exist in the company.